The impact of land development on surface runoff and the effect on existing drainage system (ITM area) / Mohamad Azman Mohamad - Mohamad, Mohamad Azman (1992)
Nowadays there are many developments in ITM area. These development project will have a significant impact to surface runoff and1 existing: drainage system. This study will try to relate the impact of land development to surface runoff and the effect on existing drainage system at the ITM campus, Shah Alam. A data base to monitor the performance of existing drainage system is set up to facilitate maintenance of the drainage system.